2020
DOI: 10.1182/bloodadvances.2020001565
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly expanded partially HLA DRB1–matched fungus-specific T cells mediate in vitro and in vivo antifungal activity

Abstract: Invasive fungal infections are a major cause of disease and death in immunocompromised hosts, including patients undergoing allogeneic hematopoietic stem cell transplant (HSCT). Recovery of adaptive immunity after HSCT correlates strongly with recovery from fungal infection. Using initial selection of lymphocytes expressing the activation marker CD137 after fungal stimulation, we rapidly expanded a population of mainly CD4+ T cells with potent antifungal characteristics, including production of tumor necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Both Rag1 -/and NSG mice were more susceptible to infection compared to wild-type mice at 3 days post infection, as shown by increased fungal burden and more severe histopathology (Figure 4). Conversely, at 7 days post infection, while NSG mice were still more susceptible to infection, in agreement with published data [18], Rag1 -/mice appeared more resistant, as shown by improved histopathology and a trend towards a reduced fungal burden (Figure 4).…”
Section: The Composition Of the Lung Microbiome And The Levels Of Scfas Are Shaped By The Immune Systemsupporting
confidence: 91%
See 1 more Smart Citation
“…Both Rag1 -/and NSG mice were more susceptible to infection compared to wild-type mice at 3 days post infection, as shown by increased fungal burden and more severe histopathology (Figure 4). Conversely, at 7 days post infection, while NSG mice were still more susceptible to infection, in agreement with published data [18], Rag1 -/mice appeared more resistant, as shown by improved histopathology and a trend towards a reduced fungal burden (Figure 4).…”
Section: The Composition Of the Lung Microbiome And The Levels Of Scfas Are Shaped By The Immune Systemsupporting
confidence: 91%
“…Both Rag1 -/-and NSG mice were more susceptible to infection compared to wild-type mice at 3 days post infection, as shown by increased fungal burden and more severe histopathology (Figure 4). Conversely, at 7 days post infection, while NSG mice were still more susceptible to infection, in agreement with published data [18], Rag1 -/-mice appeared more resistant, as shown by improved histopathology and a trend towards a reduced fungal burden (Figure 4). We evaluated the composition of the lung microbiome in these mice and found significant differences in compositional structure at the phylum level between the different groups, as measured by the Jaccard (p = 0.007) and Bray-Curtis (p = 0.016) indexes.…”
Section: The Composition Of the Lung Microbiome And The Levels Of Scfas Are Shaped By The Immune Systemsupporting
confidence: 91%
“…Ex vivo generated Rhizopus oryzae-specific T cells cross-reacted with either Aspergillus fumigatus or Rhizopus (microsporus, pusillus), Mucor circinelloides, Penicillium chrysogenum and Candida albicans [71,77]. Cross-protective immunity was also documented on multi-FSTs [59,76,79] and mp-STs targeting 3 viruses and Aspergillus fumigatus [81,82]. These data suggest an enhanced breadth of fungal recognition, however, whether the broad anti-fungal crossimmunity observed in vitro can provide global fungal protection in vivo, remains to be answered in clinical trials.…”
Section: Broad Protection Against Multiple Pathogensmentioning
confidence: 97%
“…Although FSTs have been shown to increase the resistance against Aspergillus fumigatus infection or prolong the survival of mice with invasive pulmonary mycosis [59][60][61], as of today, and in contrast to the numerous VST trials, there are only two completed, clinical trials of adoptive T cell immunotherapy against fungal diseases [41,62]. In the first study, conducted 16 years ago, Perrucio et al showed that the administration of anti-Aspergillus T cell clones was safe, enhanced the control of Aspergillus antigenemia and improved the survival of transplanted patients with invasive aspergillosis as compared to the control cohort not receiving immunotherapy (survived patients 9/10 vs. 7/13, respectively).…”
Section: Harnessing T Cells To Control Fungal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation